Processing bovine intestinal mucosa to active heparin removes spiked BSE agent. (September 2020) - Andrews, Omozusi; Bett, Cyrus; Shu, Qin; Kaelber, Nadine; Asher, David M.; Keire, David; Gregori, Luisa
Abstract: Heparin is an anticoagulant sourced from animal tissues. In the 1990s, bovine-sourced heparin was withdrawn from the U.S. market due to a theoretical concern that the bovine spongiform encephalopathy (BSE) agent might contaminate crude heparin and spread to humans as variant Creutzfeldt-Jakob disease. Only porcine intestinal heparin is now marketed in the U.S. FDA has encouraged the reintroduction of bovine heparin. We applied a scaled-down laboratory model process to produce heparin as an active pharmaceutical ingredient (API) starting from bovine intestinal mucosa. The process consisted of two phases. To model the first phase, we applied enzymatic proteolysis, anionic resin separation and methanol precipitation of crude heparin. Bovine intestinal mucosa was spiked with BSE or scrapie agents. We assayed BSE- or scrapie-associated prion protein (PrP TSE ) using the Real-Time Quaking-Induced Conversion (RT-QuIC) assay at each step. The process reduced PrP TSE by 4 log10 and 6 log10 from BSE-spiked and scrapie-spiked mucosa, respectively. To model the entire process, we spiked mucosa with scrapie agent and produced heparin API, reducing PrP TSE by 6.7 log10 . The purification processes removed large amounts of PrP TSE from the final products. Heparin purification together with careful sourcing of raw materials should allow safely reintroducing bovine heparin in the U.S.